Agmatine Alleviates Epileptic Seizures and Hippocampal Neuronal Damage by Inhibiting Gasdermin D-Mediated Pyroptosis - Xueying Li; Jiahe Lin; Yingjie Hua; Jiaoni Gong; Siqi Ding; Yanru Du; Xinshi Wang; Rongyuan Zheng; Huiqin Xu (Frontiers Media S.A., 2021)
Background: Epilepsy is a common neurological disease, and neuroinflammation is one of the main contributors to epileptogenesis. Pyroptosis is a type of pro-inflammatory cell death that is related to epilepsy. Agmatine, has anti-inflammatory properties and exerts neuroprotective effects against seizures. Our study investigated the effect of agmatine on the core pyroptosis protein GSDMD in the context of epilepsy.Methods: A chronic epilepsy model and BV2 microglial cellular inflammation model were established by pentylenetetrazole (PTZ)-induced kindling or lipopolysaccharide (LPS) stimulation. H&E and Nissl staining were used to evaluate hippocampal neuronal damage. The expression of pyroptosis and inflammasome factors was examined by western blotting, quantitative real-time PCR, immunofluorescence and enzyme-linked immunosorbent assay (ELISA).Results: Agmatine disrupted the kindling acquisition process, which decreased seizure scores and the incidence of full kindling and blocked hippocampal neuronal damage. In addition, agmatine increased BV2 microglial cell survival in vitro and alleviated seizures in vivo by suppressing the levels of PTZ-induced pyroptosis. Finally, the expression of TLR4, MYD88, phospho-IκBα, phospho-NF-κB and the NLRP3 inflammasome was significantly upregulated in LPS-induced BV2 microglial cells, while agmatine suppressed the expression of these proteins.Conclusions: Our results indicate that agmatine affects epileptogenesis and exerts neuroprotective effects by inhibiting neuroinflammation, GSDMD activation, and pyroptosis. The inhibitory effect of agmatine on pyroptosis was mediated by the suppression of the TLR4/MYD88/NF-κB/NLRP3 inflammasome pathway. Therefore, agmatine may be a potential treatment option for epilepsy.